Job satisfaction among primary school personnel in Madagascar - Gamero-Burón, Carlos; Lassibille, Gérard (My University, 2016)
This article analyzes the job satisfaction of primary school teachers in Madagascar. Based on the estimation of multilevel models, low wages and problems getting paid, job insecurity, lack of in-service training, high pupil-teacher ratios, and lack of basic infrastructure and teaching materials are identified as the main reasons for dissatisfaction. Principals’ control of teachers’ activities also adversely affects satisfaction, suggesting that, in Malagasy schools, neither school directors nor teachers have succeeded in adopting organizational cultures based on cooperation among their members. These results are likely to stimulate debates on educational policy, both in Madagascar and in many other developing countries.
Keywords: Condiciones de trabajo; Profesores de enseñanza primaria - Madagascar; Job satisfaction; Multilevel models; Primary education